EVALUATING THE KINETICS OF SODIUM- IODIDE SYMPORTER UPREGULATION IN RE-DIFFERENTIATION THERAPY CLINICAL TRIAL FOR ADVANCED THYROID CANCER - Peiling, Samantha Yang; Loke, Kelvin Siu Hoong; Chong, Wan Qin; Ng, Chee Eng; Kong, Li Ren; Goh, Boon Cher (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES MAPK hyperactivation, such as via BRAFV600E mutation, is commonly detected in radioactive iodine (RAI)-refractory thyroid cancers with suppression of sodium-iodide symporter (NIS). We hypothesize that short treatment course with MAPK blockade could suffice in upregulating NIS, while sustained 4-6 weeks treatment in current regimens could predispose to resistance. METHODOLOGY We conducted a phase II trial using BRAF and MEK inhibitors, dabrafenib and trametinib (DT) to examine the kinetics of NIS upregulation in RAI-refractory thyroid cancer with MAPK signaling pathway mutation. Iodide uptake was assessed using I-124 PET-CT scan at baseline, after 1-2 weeks and 4 weeks of DT. If there was adequate iodide retention, RAI was administered. The primary outcome was the proportion of patients attaining tumour lesional dosimetry of ≥20 Gy with I-131 dose of ≤300 mCi. Secondary outcomes included safety, response rate, progression-free survival, and thyroglobulin response. This research has been approved by an ethics committee. RESULTS Seven patients with activating BRAF and RAS mutations were recruited. Five out of 7 patients (71%) attained iodine uptake: 2 after 1-2 weeks, 3 after 4 weeks of DT. Adverse event (AE) was seen in 6 out of 7 patients (86%). Most had grade 1-2 AE, except 2 with grade 3 AE (neutropenia, severe lethargy). At 6-month time point, 80% (4/5) had thyroglobulin reduction, and 5 patients had repeat scan; 3 had partial response (60%). CONCLUSION In our patients who responded to re-differentiation therapy, 40% responded with only 1-2 weeks of DT. Identification of early response predictors could guide treatment duration.